Preconception and prenatal urinary concentrations of phenols and birth size of singleton infants born to mothers and fathers from the Environment and Reproductive Health (EARTH) study. (May 2018) - Messerlian, Carmen; Mustieles, Vicente; Minguez-Alarcon, Lidia; Ford, Jennifer B.; Calafat, Antonia M.; Souter, Irene; Williams, Paige L.; Hauser, Russ; ,
Abstract: Background: Although pregnancy concentrations of some phenols have been associated with infant size at birth, there is limited data on the effect of preconception exposure. Objective: We aimed to examine paternal and maternal preconception and maternal prenatal urinary phenol concentrations in relation to birth weight and head circumference. Methods: We evaluated 346 singletons born to 346 mothers and 184 fathers (184 couples) from a prospective preconception cohort of subfertile couples from the Environment and Reproductive Health (EARTH) Study in Boston, USA. We used multiple urine samples collected before the index pregnancy in both men and women to estimate mean preconception urinary benzophenone-3, triclosan, butylparaben, propylparaben, methylparaben, or ethylparaben concentrations. We also estimated mean maternal prenatal urinary phenol concentrations by averaging trimester-specific urine samples. Birth weight and head circumference were abstracted from delivery records. We estimated the association of natural log-phenol concentrations with birth outcomes using multivariable linear regression models, adjusting for known confounders. Results: In adjusted models, each log-unit increase in paternal preconception benzophenone-3 concentration was associated with a 137 g increase in birth weight (95% CI: 60, 214). Additional adjustment for prenatal benzophenone-3 concentration strengthened this association. None of the maternal preconception phenol concentrations were associated with birth weight. However, maternal prenatal triclosan concentrations were associated with a 38 g decrease in birth weight (95% CI: −76, 0). Few associations were observed between phenols and head circumference except for a decrease of 0.27 cm (95% CI: −54, 0) in relation to maternal preconception methylparaben concentration. Conclusions: Although our findings should be interpreted in light of inherent study limitations, these results suggest potential evidence of associations between some paternal or maternal phenol concentrations and birth size. Highlights: Pregnancy concentrations of some phenols have been associated with infant size at birth. There is limited data on the effect of paternal and maternal preconception exposure. Some phenol concentrations were associated with birth size, however, results should be interpreted cautiously.